A Call to Action for Anticoagulation Stewardship to Address Suboptimal Thromboprophylaxis Practices for at-Risk Non-Orthopedic Surgical Patients in Vietnam: An Explanatory Sequential Mixed-Methods Study - Nguyen TTT; Tong HT; Nguyen HTL; Nguyen TD (Vascular Health and Risk Management)
Thuy Thi Thu Nguyen,1 Huyen Thanh Tong,2 Huong Thi Lien Nguyen,1 Trung Duc Nguyen2 1Department of Clinical Pharmacy, Faculty of Pharmacology - Clinical Pharmacy, Hanoi University of Pharmacy, Hanoi, Vietnam; 2Department of Pharmacy, 108 Military Central Hospital, Hanoi, VietnamCorrespondence: Trung Duc Nguyen, Department of Pharmacy, 108 Military Central Hospital, 1 Tran Hung Dao Street, Hai ba Trung District, Hanoi, 10000, Vietnam, Email Trungnd@benhvien108.vnPurpose: This study aimed to investigate the current practices of VTE prophylaxis in patients undergoing abdominal-pelvic surgery (PAS) and to identify the factors that influence surgeons’ practice of VTE prophylaxis.Patients and Methods: This two-phase explanatory sequential mixed-method study used chart audits followed by semi-structured interviews based on the theoretical domain framework (TDF). During Phase I, quantitative data from 240 medical records of patients with PAS in April 2023 were audited to measure adherence rates to the standard thromboprophylaxis guidelines. In Phase II, in-depth interviews with 16 surgeons were conducted and analyzed using thematic content analysis based on the TDF framework to understand the determinants of thromboprophylaxis in patients with PAS.Results: Audits of 240 medical records of patients showed the rate of appropriate prophylactic methods was low (11.7%). For patients on anticoagulant prophylaxis, adherence rates regarding drug selection and dosage were high (100% and 89.3%, respectively), whereas adherence rates regarding time of initiation and length of prophylaxis were low (50% and 28.6%, respectively). A qualitative analysis identified 12 theoretical domains relevant to thromboprophylaxis practices among surgeons. The most encountered barriers included concerns about bleeding risk, resource issues, low beliefs about preventive benefits for certain patients with PAS, inadequate knowledge and training, and a lack of protocol and policy. The most encountered enablers included positive beliefs in prophylaxis benefits, mandatory policy and computerized supportive tools, thromboprophylaxis set as patient safety goals, leadership and multidisciplinary working, and training.Conclusion: Significant quality gaps were present in VTE prevention practice for abdominal-pelvic surgical patients, and multiple coexisting factors prevented the full adoption of practice standards. The implementation of an anticoagulation stewardship program is essential for addressing practical issues.Keywords: venous thromboembolism prevention, abdominopelvic surgery, guideline adherence, influencing factors, mixed-methods study, anticoagulant stewardship